2015
DOI: 10.3168/jds.2014-9188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding 25-hydroxyvitamin D3 with a negative cation-anion difference diet on calcium and vitamin D status of periparturient cows and their calves

Abstract: Holstein cows (>1 gestation) were fed 1 of 3 diets during the last 13 d of gestation (ranged from 22 to 7 d). The control diet (16 cows) was formulated to provide 18,000 IU/d of vitamin D3 and had a dietary cation-anion difference (DCAD) of 165mEq/kg (DCAD=Na + K - Cl - S). The second diet (DCAD + D) provided the same amount of vitamin D3 but had a DCAD of -139mEq/kg (17 cows). The third diet (DCAD + 25D) had no supplemental vitamin D3 but provided 6mg/d of 25-(OH) vitamin D3 [25-(OH)D3] with a DCAD of -138mEq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
48
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 41 publications
8
48
0
4
Order By: Relevance
“…Another mechanism of action for low DCAD diets in preventing hypocalcemia in the transition period is through increases in urinary Ca excretion prepartum. Decreasing DCAD consistently increases urinary Ca excretion to some degree (Gaynor et al, 1989;Joyce et al, 1997;Goff et al, 2014), and the magnitude of increase is highly correlated with urine pH (Grünberg et al, 2011;Weiss et al, 2015). A potential mechanism for this effect on urine Ca flux is a direct inhibition of Ca reabsorption from the filtrate in the kidney due to the additional acid load (Stacy and Wilson, 1970), which is supported by the strong linear relationship observed between urine pH and urine Ca-to-creatinine ratio in the current trial as well as in a previous study (Grünberg et al, 2011).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Another mechanism of action for low DCAD diets in preventing hypocalcemia in the transition period is through increases in urinary Ca excretion prepartum. Decreasing DCAD consistently increases urinary Ca excretion to some degree (Gaynor et al, 1989;Joyce et al, 1997;Goff et al, 2014), and the magnitude of increase is highly correlated with urine pH (Grünberg et al, 2011;Weiss et al, 2015). A potential mechanism for this effect on urine Ca flux is a direct inhibition of Ca reabsorption from the filtrate in the kidney due to the additional acid load (Stacy and Wilson, 1970), which is supported by the strong linear relationship observed between urine pH and urine Ca-to-creatinine ratio in the current trial as well as in a previous study (Grünberg et al, 2011).…”
supporting
confidence: 81%
“…Early work on low DCAD feeding consistently showed decreased DMI during the prepartum period for negative DCAD rations, as summarized in the metaanalysis by Charbonneau et al (2006). More recently, the combination of minimizing basal dietary cations to reduce the amount of supplemental anions that need to be included in the ration, as well as the adoption of more palatable commercial anion sources, has resulted in several trials in which anions were supplemented to reach urine pH values close to the range of the current trial with no effect on prepartum intake (Moore et al, 2000;DeGroot et al, 2010;Weich et al, 2013;Weiss et al, 2015) or minimal effects that did not result in evidence of impaired metabolic health (Ramos-Nieves et al, 2009). The quadratic effect on prepartum intake in our trial suggested that cows fed MED had the highest intake in the prepartum period, with the lowest intake in cows fed LOW; however, absolute differences between groups were relatively small and we found no effects of treatment on peripartum plasma concentrations of glucose, NEFA, or BHB.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Due to the use of these strategies, the prepartum cows should develop a mild metabolic acidosis. As a result, the activity of PTH will be enhanced, with an expected response of less hypocalcemia around parturition (2, 15). …”
Section: Discussionmentioning
confidence: 99%